2009
DOI: 10.1017/s0033291709005376
|View full text |Cite
|
Sign up to set email alerts
|

The effect of post-injury depression on return to pre-injury function: a prospective cohort study

Abstract: Background-Millions of people seek emergency department care for injuries each year, the majority for minor injuries. Little is known about the effect of psychiatric co-morbid disorders that emerge after minor injury on functional recovery. This study examined the effect of post-injury depression on return to pre-injury levels of function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
2
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 48 publications
2
36
2
1
Order By: Relevance
“…Clinicians approach emotional recovery from a more pathological lens, speaking of PTSD and depression, and this is consistent with the preponderance of the current literature 29,30 . Importantly, stakeholder groups differed in their perspectives of recovering emotional stability.…”
Section: Discussionsupporting
confidence: 74%
“…Clinicians approach emotional recovery from a more pathological lens, speaking of PTSD and depression, and this is consistent with the preponderance of the current literature 29,30 . Importantly, stakeholder groups differed in their perspectives of recovering emotional stability.…”
Section: Discussionsupporting
confidence: 74%
“…1,6 Depressive symptoms and emotional disturbances appear to be present regardless of the nature of the injury. Richmond et al 7 found that 18% of patients displayed major depression, depression not otherwise specified, or dysthymia a year after a minor injury. Additional authors 1,5,8,9 have reported increased incidences of depression and emotional disturbances after both chronic and serious injuries.…”
mentioning
confidence: 99%
“…Depresyonda olan bireyler ise yaralanma sonrası yıl boyunca yaralanma öncesi düzeylere geri dönememekte ve yaralanmaya bağlı bu psikolojik tepkiler, fonksiyonel bozukluklara neden olabilmektedir (29). Kas--iskelet sistemi ağrılarında kinezyofobi ile ağrı şiddeti, fonksiyonel kısıtlılık ve psikolojik özellikler arasında ilişki bulunmaktadır (30).Bu sonuçlardan farklı olarak servikal diskopatili hastalarda, psikolojik ve ağrı ile ilişkili klinik verilerin kinezyofobide belirleyiciler olmadığını belirten sonuçlar bulunmaktadır (28 Psikolojik faktörlerden sadece müsabaka kaygısının spor yaralanmasında etkili olduğunu, genel kaygının (anksiyete) ise bu yaralanmalarda etkisinin olmadığını belirten çalışmalar bulunmaktadır (31).…”
Section: Discussionunclassified